Labor drops: Experimental evidence on the return to additional labor in microenterprises - de Mel, S; McKenzie, D; Woodruff, C (American Economic Association, 2019)
A field experiment in Sri Lanka provided wage subsidies to randomly chosen microenterprises to test whether hiring additional labor benefits such firms, and whether a short-term subsidy can have a lasting impact on firm employment. Using 12 rounds of surveys to track dynamics four years after treatment, we find that firms increased employment during the subsidy period. Treated firms were more likely to survive, but there was no lasting impact on employment, and no effect on profitability or sales either during or after the subsidy period. There is some heterogeneity in effects; the subsidies have more durable effect on manufacturers.